Effects of the monolaurin based feed additive MGOsyn on methane production, rumen fermentation, and microbial communities using rumen fluid from Hanwoo steers in an in vitro study - Park, Mi Ae; Son, Seoyun; Lim, Da Jung; Yu, Hee Seop; Yoon, Yong Hee; Kim, Seon-Ho; Lee, Sang-Suk; Kim, Dae-Hyuk; Kim, Yangseon (Frontiers in Microbiology, 2025)
Reducing enteric methane emissions from livestock mitigates environmental impact and improves production efficiency. This initial in vitro study investigated the potential of MGOsyn, a new feed additive composed of monolaurin, garlic, and oregano with synergistic antimethanogenic properties, to influence rumen fermentation parameters, methane production, and the structure of bacterial and archaeal communities. The experiment was conducted as a batch culture using rumen fluid collected from Hanwoo steers with ground concentrate as the substrate. MGOsyn, a monolaurin based feed additive (GRAS, Generally Recognized As Safe), was supplemented at three different concentrations. 0% (MGOsyn CON), 0.1% (MGOsyn LOW), and 0.2% (MGOsyn HIGH) of the total fermentation volume. After 24 h of incubation at 39 °C, MGOsyn increased propionate production by 50% in a dose dependent manner, while reducing methane emission by 61%, acetate proportion and the acetate to propionate ratio. Microbial community analyses revealed that MGOsyn effectively altered the ruminal microbiome. The bacterial community exhibited an increased relative abundance of succinate and propionate producing bacteria, such as Succinivibrio, Succiniclasticum, Candidatus Saccharimonas, Succinivibrionaceae UCG-002, and Prevotella 7 which are involved in hydrogen sink pathways following MGOsyn supplementation. Considering the archaeal community, the abundance of Methanomethylophilaceae decreased with MGOsyn supplementation compared with that in the control, whereas Methanosphaera increased in the high MGOsyn supplementation group. To further explore the underlying mechanisms of methane mitigation, we performed correlation and intercorrelation analyses between fermentation parameters and microbial taxa, along with functional predictions of relevant metabolic pathways. Succinate/propionate producing bacteria showed strong positive correlations with MGOsyn supplementation and propionic acid production, and strong negative correlations with acetic acid production, the acetate to propionate ratio, and methane production. These findings suggest that MGOsyn effectively mitigates methane emissions by stimulating propionate formation through the hydrogen sink pathway. By altering the ruminal microbial community toward enhanced propionate production, MGOsyn shows promise as a functional feed additive for improving rumen fermentation efficiency and reducing methane output in ruminants.